PENGARUH FUNGSI PENGAWASAN TERHADAP KINERJA PEGAWAI PADA KANTOR PEKERJAAN UMUM KABUPATEN PUNCAK JAYA - palinggi, yohanes; rusno; mariani manika, yuni (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2025)
This study aims to analyze the effect of supervision on the performance of employees at the Office of Manpower Office of Puncak Jaya City in 2023, in terms of internal and external monitoring. This research data is obtained from the method of data presentation of the results of responses of respondents (questionnaires), as well as other research results relevant to the object under study, in this case the primary data from the government agencies Manpower Office of Puncak Jaya. The statistical analysis used in this study is simple regression analysis using SPSS 22 program. The findings of this study indicate that the supervisory variables consisting of external supervision, internal and control audits significantly influence the performance of employees of the Manpower Office of Puncak Jaya City, as evidenced by the value of significance of 0.025 <0.05.